Pelatihan Pembuatan Pupuk dan Pestisida Organik bagi Petani Cabai di Desa Tajau Landung Kabupaten Banjar: Training for producing Organic Fertilizers and Pesticides for Chili Farmers in Tajau Landung Village, Banjar District - Mariana Mariana; Elly Liestiany; Ismed Setya Budi; Samharinto Samharinto; Muhammad Indar Pramudi; Dewi Fitriyanti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Chili is one of the vegetable commodities that have excellent and promising business opportunities in Tajau Landung Village. In this village there are 16 farmer groups and 75% of them grow chilies, both large chilies and cayenne peppers. Pesticides and chemical fertilizers are the main production factors in chili farming. Prices and access to subsidized pesticides and chemical fertilizers are a constraint for farmers, and their residues have a negative impact on consumers and the environment. This activity aims to provide training to farmers in Tajau Landung Village to produce organic fertilizers and pesticides. The activity began with counseling about Chili Pests and Diseases and how to control them organically, as well as pretest and posttest using a questionnaire. The next activity was training on making bokasi fertilizer enriched with Trikoberas, and PGPR (Plant Growth Promoting Rhizobacteria). Based on the results of the evaluation, it was concluded that there was an increase in participants' understanding of chili pests and diseases and their control before and after being given counseling. %). Participants already have skills in making organic bokasi fertilizer from water hyacinth and kiyambang weeds, PGPR, and Trikoberas added to bokasi fertilizer to become Trikokompos, and showed very good acceptability assessment results.